"Hypotheses fingimus": Cartesian Natural Philosophy - Daniel Špelda (Teorie vědy, 2021)
In this paper, I would like to present the methodological views of two representatives of the early modern Cartesian school: Jacques Rohault and Pierre-Sylvain Régis. Firstly, I want to present the methodological objections of Cartesians to Aristotelian and Scholastic natural philosophy. Then, I want to show how Cartesians strived for a combination of empirical and speculative procedures in their explanations of natural processes. Lastly, I would like to explain the reasons and forms of the hypothetical methodology which was significant for Cartesian natural philosophy. My aim is to refute the idea of the methodological naivety of Cartesians and point out the importance of hypothetical reasoning in the genesis of modern science.